2011
DOI: 10.1016/j.biotechadv.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Advances in carbon nanotube based electrochemical sensors for bioanalytical applications

Abstract: Electrochemical (EC) sensing approaches have exploited the use of carbon nanotubes (CNTs) as electrode materials owing to their unique structures and properties to provide strong electrocatalytic activity with minimal surface fouling. Nanofabrication and device integration technologies have emerged along with significant advances in the synthesis, purification, conjugation and biofunctionalization of CNTs. Such combined efforts have contributed towards the rapid development of CNT-based sensors for a plethora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
218
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 402 publications
(223 citation statements)
references
References 222 publications
0
218
0
Order By: Relevance
“…It is perhaps worth noting that the CNTs' electrocatalytic properties are somewhat controversial. In fact, it has been suggested that it is the presence of metal impurities introduced during the preparation of CNTs, rather than the CNTs themselves, that provides the basis of the electrocatalytic behavior (209,240,241). In addition, there is still not unanimous agreement regarding the cytotoxicity of CNTs, although some authors support that functionalization of CNTs can control it (240,241).…”
Section: Carbon Nanotubes and Graphene -An Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…It is perhaps worth noting that the CNTs' electrocatalytic properties are somewhat controversial. In fact, it has been suggested that it is the presence of metal impurities introduced during the preparation of CNTs, rather than the CNTs themselves, that provides the basis of the electrocatalytic behavior (209,240,241). In addition, there is still not unanimous agreement regarding the cytotoxicity of CNTs, although some authors support that functionalization of CNTs can control it (240,241).…”
Section: Carbon Nanotubes and Graphene -An Overviewmentioning
confidence: 99%
“…In fact, it has been suggested that it is the presence of metal impurities introduced during the preparation of CNTs, rather than the CNTs themselves, that provides the basis of the electrocatalytic behavior (209,240,241). In addition, there is still not unanimous agreement regarding the cytotoxicity of CNTs, although some authors support that functionalization of CNTs can control it (240,241). Finally, an important aspect to consider is the relatively high cost of producing and purifying CNTs (although this is decreasing over time), which may in some way explain the delay in their uptake by the industry (235,240).…”
Section: Carbon Nanotubes and Graphene -An Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several methods to deposit carbon nanotubes on metal electrodes. Electrodeposition is by far one of the most precise and reliable techniques to deposit carbon nanotubes even on sub-mm electrodes (Vashist et al, 2011). Electrodeposition is a method to arrange macromolecules by applying a voltage on an electrode.…”
Section: Introductionmentioning
confidence: 99%